Suplementasi Calcitriol Efektif untuk Penanganan Nefrosis Akut dan Osteoporosis pada Tikus Dewasa (CALCITRIOL SUPPLEMENTATION EFFECTIVE FOR ACUTE NEPHROSIS AND OSTEOPOROSIS TREATMENTS IN ADULT RATS) - Hartiningsih, Hartiningsih; Tanasib, Mario Afra Gracia Kristiano; Fatmawati, Rekha; Anggraeni, Devita (Jurnal Veteriner; Vol 21 No 1 (2020), 2020)
High phosphor diet caused acute nephrosis and osteoporosis. 1,25-dihidroksivitamin D3 supplementation doesn’t changed the structure of kidney and effective for osteoporosis treatment in ovariectomized rats. The objective of the research was to study the effectivity of calcitriol for acute nephrosis and osteoporosis treatments in adult Wistar rats induced high phosphor diet. Twenty five female Wistar rats, at the age of 8 weeks were randomly divided into five groups (Nk, N, ODk, OD, and OD40). Rats in Nk and N groups were fed standard died, while rats in ODk, OD, and OD40 group were fed high phosphor diet (Ca:P=0,6%:2,4%) for 8 weeks for acute nephrosis and osteoporosis induction. As control acute nephrosis and osteoporosis, after 8 weeks of induction, blood samples were taken from retro orbital plexus for calcium and phosphor analysis. Nk dan ODk rats were then euthanized, right tibia and kidney were taken for histopathological examination using hematoxylin and eosin stain. The results showed that calcium and phosphor levels of ODk were not significantly different compared with Nk. Histopathological analysis of the kidney and proksimal tibia epiphysis in ODk group were showed acute nephrosis and osteoporosis. For the treatment of acute nephrosis and osteoporosis, OD40 rats was given standar diet and calcitriol 40 ng, meanwhile, N and OD  rats were only given fed with standar diet  for 5 weeks. At the end of the study, blood samples were taken from retro orbital plexus for calcium and phosphor analysis.  N, OD, and OD40 rats were then euthanized, right  tibia and kidney were taken for histopathological examination using hematoxylin and eosin stain. The results showed that calcium and phosphor levels of OD were not different compared with N. Calcium levels of OD40 was not different compared with N, meanwhile phosphor levels of OD40 were significantly increased compared with N. Histopathologically, kidney of OD40 was showed improvement that dose to normal. Meanwhile, proximal tibial epiphysis of OD40 were shown more trabecular bone speculum and less adipocyte in the bone marrow of epiphysis compared with OD. In conclusion, calcitriol 40ng/day supplementation in adult rats for 8 weeks was effective for acute nephrosis and osteoporosis treatments.